Pesticide analysis using nanoceria-coated paper-based devices as a detection platform - Souksanh Nouanthavong (2018)
© 2016 The Royal Society of Chemistry. We report the first use of a paper-based device coated with nanoceria as a simple, low-cost and rapid detection platform for the analysis of organophosphate (OP) pesticides using an enzyme inhibition assay with acetylcholinesterase (AChE) and choline oxidase (ChOX). In the presence of acetylcholine, AChE and ChOX catalyze the formation of H2O2, which is detected colorimetrically by a nanoceria-coated device resulting in the formation of a yellow color. After incubation with OP pesticides, the AChE activity was inhibited, producing less H2O2, and a reduction in the yellow intensity. The assay is able to analyze OP pesticides without the use of sophisticated instruments and gives detection limits of 18 ng mL-1and 5.3 ng mL-1for methyl-paraoxon and chlorpyrifos-oxon, respectively. The developed method was successfully applied to detect methyl-paraoxon in spiked vegetables (cabbage) and a dried seafood product (dried green mussel), obtaining ∼95% recovery values for both sample types. The spiked samples were also analyzed using LC-MS/MS as a comparison to the developed method and similar values were obtained, indicating that the developed method gives accurate results and is suitable for OP analysis in real samples.